2016
DOI: 10.1002/jsfa.7877
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant activity of rice protein affected by alkaline degree and gastrointestinal protease digestion

Abstract: The present study indicates that antioxidant capacity of RP could be more readily depressed by strict alkali degree and affected by gastrointestinal proteases. Results suggest that alkali extraction is a vital process to regulate the antioxidant activity of RP through modifying the compositions of amino acids, which are dependent on alkali magnitude. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
(146 reference statements)
2
25
0
Order By: Relevance
“…Rice protein can exert antioxidant activity to reduce oxidative stress. 15,16,[24][25][26] The present study demonstrated that rice protein could reduce ROS-derived DNA damage, which was attributable to the stimulation of an antioxidative response to rice protein intake. More significantly, results indicated that the effect of rice protein on reducing DNA damage was attributable to the activation and the up-regulation of the ATM-Chk2-p53 pathway in growing and adult rats.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Rice protein can exert antioxidant activity to reduce oxidative stress. 15,16,[24][25][26] The present study demonstrated that rice protein could reduce ROS-derived DNA damage, which was attributable to the stimulation of an antioxidative response to rice protein intake. More significantly, results indicated that the effect of rice protein on reducing DNA damage was attributable to the activation and the up-regulation of the ATM-Chk2-p53 pathway in growing and adult rats.…”
Section: Discussionsupporting
confidence: 50%
“…Rice protein can exert antioxidant activity to reduce oxidative stress . The present study demonstrated that rice protein could reduce ROS‐derived DNA damage, which was attributable to the stimulation of an antioxidative response to rice protein intake.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…It is suggested that sulfur‐containing amino acid plays a key role in antioxidant defense . With this in view, the effect of l ‐ methionine on inducing the endogenous antioxidant response was focused on in this study.…”
Section: Discussionmentioning
confidence: 99%